2016
DOI: 10.1002/ajmg.a.37542
|View full text |Cite
|
Sign up to set email alerts
|

Decline of CSF orexin (hypocretin) levels in Prader–Willi syndrome

Abstract: Prader-Willi syndrome is a congenital neurodevelopmental disorder resulting from deletion of the paternal copies of genes within the chromosome region 15q11-q13. Patients with Prader-Willi syndrome often exhibit excessive daytime sleepiness, excessive appetite, and obesity. As is the case in narcolepsy, orexin (hypocretin) may be responsible for these symptoms. However, reports showing cerebrospinal fluid orexin levels in Prader-Willi syndrome patients have been limited. The aim of this study was to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
(39 reference statements)
0
21
0
2
Order By: Relevance
“…Among symptomatic narcolepsy, Prader-Willi syndrome, myotonic dystrophy type1 and NPC were known as congenital and developmental disorders [25]. We reported that orexin levels with Prader-Willi syndrome and myotonic dystrophy type1 were higher than idiopathic narcolepsy and lower than idiopathic hypersomnia [28,29]. The orexin levels of NPC were also same as above two diseases (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Among symptomatic narcolepsy, Prader-Willi syndrome, myotonic dystrophy type1 and NPC were known as congenital and developmental disorders [25]. We reported that orexin levels with Prader-Willi syndrome and myotonic dystrophy type1 were higher than idiopathic narcolepsy and lower than idiopathic hypersomnia [28,29]. The orexin levels of NPC were also same as above two diseases (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Dysregulation of the OX system has been reported in a few clinical studies, although to date, the results remain contradictory. One study described an increase in the OX-A level in PWS subjects [47], while another showed a decrease in the peptide in the cerebrospinal fluid [11]. Taken together, these findings call for an alteration of the OX system in PWS, although the contrasting results may also suggest that the loss of function of paternal alleles within the PWS region results in an increased phenotypic variance.…”
Section: Discussionmentioning
confidence: 96%
“…REM sleep intrusions have been reported in several clinical studies in which PWS subjects manifest narcolepsy and express symptoms such as sleep attacks during active wakefulness, cataplexy (a transient loss of muscle tone during wakefulness), sleep paralysis and sleep fragmentation [8]. Narcolepsy is a sleep condition that causes the loss of hypothalamic OX neurons (also known as hypocretin; HCRT) [9], and previous studies have observed that subjects with PWS show OX alterations [10][11][12].…”
mentioning
confidence: 99%
“…In some individuals, hypersomnia may be due to hypothalamic dysfunction. In others, it is associated with a narcolepsy-like phenotype that includes sleep-onset REM periods and sometimes cataplexy [85,86]. Orexin-A (hypocretin-1), a neuropolypeptide important in maintaining wakefulness, is absent or found at very low levels in individuals with narcolepsy type 1 with cataplexy [87,88].…”
Section: Excessive Daytime Sleepiness and Rem Sleep Disturbancesmentioning
confidence: 99%
“…Orexin-A (hypocretin-1), a neuropolypeptide important in maintaining wakefulness, is absent or found at very low levels in individuals with narcolepsy type 1 with cataplexy [87,88]. Intermediate levels of orexin-A are also seen in cerebral spinal fluid of some PWS patients with excessive daytime sleepiness [86,89]. Some success has been reported using the stimulant modafinil for PWS patients with hypersomnia [90,91]; however, it is important to ensure that hypersomnia in these patients is not secondary to severe OSA prior to starting a stimulant.…”
Section: Excessive Daytime Sleepiness and Rem Sleep Disturbancesmentioning
confidence: 99%